DOI: 10.31274/rtd-180813-8007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of calves with Mycoplasma dispar

Abstract: INFORMATION TO USERSThis was produced from a copy of a document sent to us for microfihning. While the most advanced technological means to photograph and reproduce this document have been used, the quality is heavily dependent upon the quality of the material submitted.The following explanation of techniques is provided to help you understand markings or notations which may appear on this reproduction. 1. The sign or "target" for pages apparently lacking from the document photographed is "Missing Page(s)". If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
5
1
Order By: Relevance
“…Statistical tendency was observed between M. dispar and tachypnea. In an experimental infection of M. dispar in calves, Ribeiro (1979) reported that only one calf showed clinical signs of BRD and that M. dispar pneumonia might be a mild infection.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical tendency was observed between M. dispar and tachypnea. In an experimental infection of M. dispar in calves, Ribeiro (1979) reported that only one calf showed clinical signs of BRD and that M. dispar pneumonia might be a mild infection.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding M. dispar, our data indicated an association between this bacterium and tachypnea and mixed dyspnea. In an experimental infection with M. dispar in calves , most calves showed no clinical signs of BRD . However, only 1 calf showed persistent nonproductive cough and dyspnea, besides increased respiratory rate and fever.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study indicated that coarse crackles and whistling were associated with the absence of M. dispar . Mycoplasma dispar is regularly isolated from bovine pneumonic lungs, but its presence has been associated with mild infection . Discrepancies in results allow researchers to continue studying these microorganisms to better understand the importance of mycoplasmas in the development of clinical signs of BRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations